STATION REZEKNE I TERRITORY WATER QUALITY - Berjoza, Lauris; Matisovs, Ivars (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2016)
In this research main purpose was to find out water reservoirs quality in station Rezekne I territory, as well was taken water sample from the ground waters. Water samples were analysed.